POLICY OF SMALL AND MEDIUM-SIZED ENTERPRISES IN CHINA - Powiertowska, Małgorzata (Acta Universitatis Nicolai Copernici. Zarządzanie, 2016)
This study is a general review of the SME sector in China. It contains criteria and definition of Chinese companies, brings special attention to traditional culture based on Confucianism, which influences the management of SME. The article also traces the SME sector reforms that have been carried out since 2000, as well as programs aimed at supporting the SME sector in China.